Investigation of the leptin levels in the blood serum of Cyprinus carpio (Linnaeus, 1758) and Capoeta trutta (Heckel, 1843) - Koprucu, S.; Algul, S. (Wiley, 2015)
Leptin is a peptide hormone secreted by adipose tissues in the various teleost fish and vertebrates. Leptin has been suggested to have an important role in a range physiological function, including regulation of food intake, reproduction, immune function, energy expenditure, lipid and carbohydrate metabolism. In this study, leptin levels in the blood serum of Cyprinus carpio and Capoeta trutta were determined. Then the results were compared between two species and between sexes of each species. In addition, leptin levels were also compared with the body weight and length of both C.carpio and C.trutta. Leptin level was analysed using available enzyme-linked immunoassay (ELISA) kit (Rat leptin ELISA kit, catalog no: SK00050-08). Leptin levels showed no significant difference (p>0.05) that in relation to between two species and between sexes of each species. It has been shown that not significantly correlated when examined correlations between the leptin level in blood serum and body weight (r=0.192, p=0.380) or length (r=0.102, p=0.644) of C.carpio. Similarly, the correlations between leptin level in blood serum and body weight (r=0.021, p=0.959) or length (r=0.123, p=0.595) of C.trutta were also not significant.
Keywords: leptin; Cyprinus carpio; Capoeta trutta; ELISA